PERGULATAN ANTARA EKONOMI DAN POLITIK DALAM PERSPEKTIF PUBLIC CHOICE - Maani, Karjuni Dt. (TINGKAP, 2013)
Separation between economics and political science have long lasted so they are not able to provide the same conclusion about the analyzed object. Economics only examine market institutional aspects without touching nonmarket social institutions. Instead of political science is very poor framework for seeing the phenomenon of economic analysis on the basis of market institutions. Public choice perspective has become a bridge that can analyze problems outside the framework of the analysis, which is based on the phenomenon of the market. This is what allows the return encounter in economics and politics in a region so that the analysis of the development of social sciences in the future is no longer compartmentalized in strict discipline, not mutually exclusive and mutually reinforce with each other. As a result of this separation of science, the social sciences experienced a major crisis due to many new phenomena, which can not be captured perfectly by the two groups of scientists. Keywords: Economics, politics, perspective, public choice